2018
DOI: 10.3390/socsci8010001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Associated to the Enrollment and Demand of Computing-Related Careers

Abstract: Despite the great need for computer-related career professionals, some universities that offer specialties to develop professionals with knowledge to cover the mention need, present a decrease in enrollment, which can cause a wide variety of problems. That is why in this paper we set out to investigate what the main factors that directly or indirectly affect student enrollment in computer-related careers are, to establish a literature-based starting point, and to help select the best possible strategy to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…According to the above diagrams (Figures 1 and 2), there is a change in the teacher-student relationship in the innovative education technologies, compared to the tradi- introduction and development of distance education is explained by the fact that traditional forms of education cannot fully cope with rapid information development and the growing social need for modern educational technologies. The introduction of distance education systems based on computer, video, multimedia, and communication technologies has allowed this problem to be solved more effectively [29,30].…”
Section: Modern Distance Learning Platformmentioning
confidence: 99%
“…According to the above diagrams (Figures 1 and 2), there is a change in the teacher-student relationship in the innovative education technologies, compared to the tradi- introduction and development of distance education is explained by the fact that traditional forms of education cannot fully cope with rapid information development and the growing social need for modern educational technologies. The introduction of distance education systems based on computer, video, multimedia, and communication technologies has allowed this problem to be solved more effectively [29,30].…”
Section: Modern Distance Learning Platformmentioning
confidence: 99%
“…Student perception and attitude about a career usually affect their choice in selecting a college course. Across investigation studies, interest was indicated as the major significant factor that influenced course choice [29,30]. However, most recent research also probed that socio-economic status has an essential relevance to students' choice of career to study [31].…”
Section: Social Interestmentioning
confidence: 99%
“…Student enrolments are essential to any higher learning institutions and tuition remains a key determinant of the proper functioning of tertiary institutions worldwide. This is due to the fact that school fees remain the main source of revenue in these institutions (Mata-López & Tobón, 2018). Indeed, shortage of student enrolments in private higher learning is considered a threat for these institutions.…”
Section: Strategies To Improve University Student Enrolmentsmentioning
confidence: 99%